2014
DOI: 10.1016/j.atherosclerosis.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma total homocysteine and carotid intima-media thickness in type 1 diabetes: A prospective study

Abstract: OBJECTIVE Plasma homocysteine (tHcy) has been positively associated with carotid intima-media thickness (IMT) in non-diabetic populations and in a few cross-sectional studies of diabetic patients. We investigated cross-sectional and prospective associations of a single measure of tHcy with common and internal carotid IMT over a 6-year period in type 1 diabetes. RESEARCH DESIGN AND METHODS tHcy levels were measured once, in plasma obtained in 1997-1999 from patients (n=599) in the Epidemiology of Diabetes Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
(57 reference statements)
2
25
1
Order By: Relevance
“…Laboratory inflammation markers have been used as predictive tools for atherosclerosis in patients with type 2 DM (36,(40)(41)(42)(43). In our study, we found no association between the inflammation markers hs-PCR and fibrinogen with subclinical atherosclerosis in patients with type 1 DM.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Laboratory inflammation markers have been used as predictive tools for atherosclerosis in patients with type 2 DM (36,(40)(41)(42)(43). In our study, we found no association between the inflammation markers hs-PCR and fibrinogen with subclinical atherosclerosis in patients with type 1 DM.…”
Section: Discussioncontrasting
confidence: 49%
“…Nitric oxide, an oxidative stress marker, also correlated with CIMT in young patients with type 1 DM, suggesting a possible role of oxidative stress in the development of atherosclerosis (20). Data from the DCCT/EDIC study have shown in patients with type 1 DM that plasma homocysteine correlates with CIMT but not with CIMT progression; based on this finding, routine homocysteine measurement in patients with type 1 DM found no support (43). Thus, further studies are needed to evaluate the clinical impact of laboratory inflammation markers in the prediction of subclinical atherosclerosis in type 1 DM.…”
Section: Discussionmentioning
confidence: 78%
“…This is supported by our finding that homocysteine level was higher in patients with hypertension and that it did not correlate with blood pressure values measured during hospitalization. Hyperglycemia, high blood pressure, and hyperhomocysteinemia [15,26,27] all accelerate atherosclerosis. Thus, we must assume that subjects with hyperhomocysteinemia have a long history of diabetes or hypertension and very high risk for atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Boosted Hcy amounts effected intensity of Coronary arterial disease (Shenoy et al, 2014). Homocysteine has effect on endothelial malfunction and is consider to be intercede by factors consisting nuclear factor-kb (NF-kb) activation, provention of endothelial nitric oxide synthase, oxidative stress and inflammation (Basu et al, 2014). It is known that in a case of atherosclerosis, Carotid intima-media thickness is noninvasive factor (Basu et al, 2014).…”
Section: Relationship Between Homocysteine and Cardiovascular Diseasementioning
confidence: 99%
“…Homocysteine has effect on endothelial malfunction and is consider to be intercede by factors consisting nuclear factor-kb (NF-kb) activation, provention of endothelial nitric oxide synthase, oxidative stress and inflammation (Basu et al, 2014). It is known that in a case of atherosclerosis, Carotid intima-media thickness is noninvasive factor (Basu et al, 2014). There is less dependence between total Hcy amounts and carotid intima media sickness in the nondiabetic groups, also it's known that the connection in the base of diabetes mellitus (DM) (Basu et al, 2014).…”
Section: Relationship Between Homocysteine and Cardiovascular Diseasementioning
confidence: 99%